The Role of Reducing Global Methane Emissions in Achieving Carbon Neutrality: Russia's Interests - L. L. Razumnova; T. E. Migaleva (Вестник Российского экономического университета имени Г. В. Плеханова, 2022)
The article analyzes the policy of reducing methane emissions as one of the directions of joint efforts of countries to curb the pace of climate change. Climate changes caused by the accumulation of methane in the atmosphere directly affect the socio-economic and political processes taking place in various regions of the world: food security, water supply, the development of military-political conflicts, the growth of international migration flows, etc. The purpose of the article is to substantiate the need and identify potential opportunities for Russia to reduce methane (CH4) emissions in the oil and gas sector. A brief description of the results of the Global Climate Summit SOR26, breakthrough solutions and problems in the field of reducing methane emissions is given. Based on the IEA's interactive database, the indicators of CH4 emissions in the oil and gas sector of the largest countries and the main categories of emissions in the oil and gas sector of Russia are described. Legislative initiatives to reduce methane emissions in the EU and Russia are considered. The article concludes that it is expedient for the Russian Federation to participate in international in international cooperation to achieve global goals in this area, in particular from the point of view of increasing the commercial attractiveness of Russian oil and gas projects and the development of green financing.